EFFECT OF DIFFERENT TYPES OF ORGANIC FERTILIZER ON SOME SECONDARY METABOLIC COMPOUNDS PRODUCT OF CACTUS (ALOE VERA L.) - & Rabee, Muneer (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was carried out on the Cactus (Aloe vera L.) , which two year old was planted in one of the fields of College of Agriculture - University of Baghdad during 2015-2016. The different organic fertilizers used in two (sewage, poultry manure and sheep manure) and the fertilizer used at two levels (5 and 7.5)% from the weight of the pot, and humic acid (Com Sol) at two levels (1.5 and 3) ml and chemical fertilizer NPK (2.5 gm) in addition to control treatment. The experiment carried out within RCBD at three replicates and four plants for each experimental unit. The results showed that the sewage treatment 7.5% significantly increased in concentration of Aloin, Aloe-emodin and Barbolin (175.6, 412.1 and 175.6 µg.gm-1 ) respectively. The treatment of NPK caused significantly increased compare with the other treatments and this treatment gives high percentage to nitrogen, phosphor and potassium which were 1.297%, 0.213% and 1.84% respectively, and also the NPK treatment gives high concentration for amino acid which were Glutamate, Lucien and Methionine  (93.44, 65.730 and 40.550) µg.gm-1 respectively.